Legal Sociological Perspective on Marriage Under the Hand (Case Study Understanding of the Cipadung Community, Bandung City) - Makruf, Solihan; Mufti, Rizal Agung; Ningsih, Lis Diana; Saebani, Beni Ahmad; Suprihatno, Andri (Dinasti Research, 2025)
This research is motivated by the phenomenon of the rampant practice of underhand marriage in the community of Cipadung Village, Bandung City, which raises various legal and social issues. This research aims to analyze the Cipadung community's understanding of underhand marriage and the factors that drive the practice. This research used a qualitative approach with a case study method, focusing on the community in a particular neighborhood to gain in-depth insights. Data was collected from religious leaders and other relevant parties using in-depth interview techniques, direct observation, and documentary studies. The data was also analyzed using descriptive-qualitative methods to identify patterns and perceptions that emerged in the community. The results of this study show that the community's understanding of Islamic law with nikah siri remains diverse and is influenced by education levels and social and economic factors. Most people understand nikah siri as religiously valid but do not understand its formal legal implications. The findings of this study suggest the need for more intensive legal education and a more effective approach by the government and religious leaders to raise public awareness of the importance of registering marriages. This is necessary to protect women's and children's rights and bring order to Indonesia's family law system.